2018
DOI: 10.1146/annurev-statistics-031017-100101
|View full text |Cite
|
Sign up to set email alerts
|

Cure Models in Survival Analysis

Abstract: When analysing time-to-event data it often happens that a certain fraction of the data corresponds to subjects that will never experience the event of interest. These event times are considered as infinite and the subjects are said to be cured. Survival models that take this feature into account are commonly referred to as cure models. This paper gives a review of the literature on cure regression models in which the event time (response) is subject to random right censoring and has a positive probability to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 87 publications
(162 reference statements)
1
114
0
Order By: Relevance
“…The possible reason for the large bias and MSE observed in the AUC estimates when using the misspecified Cox working model, in this case, can be explained by the bias in estimating the survival function for data with a cure fraction. This was well documented in Amico and Van Keilegom (). In their paper, when comparing the MCM and Cox model in a simulation study, the authors concluded that “not taking into account the presence of a cure fraction in survival data has important consequences that may lead to wrong conclusions.” In our simulations study, we also investigated the case when the data are generated for the classical Cox model (without cure) and the AUC is estimated using either the Cox or the mixture cure working model.…”
Section: Simulationssupporting
confidence: 72%
See 1 more Smart Citation
“…The possible reason for the large bias and MSE observed in the AUC estimates when using the misspecified Cox working model, in this case, can be explained by the bias in estimating the survival function for data with a cure fraction. This was well documented in Amico and Van Keilegom (). In their paper, when comparing the MCM and Cox model in a simulation study, the authors concluded that “not taking into account the presence of a cure fraction in survival data has important consequences that may lead to wrong conclusions.” In our simulations study, we also investigated the case when the data are generated for the classical Cox model (without cure) and the AUC is estimated using either the Cox or the mixture cure working model.…”
Section: Simulationssupporting
confidence: 72%
“…During the last decades, different methods for modeling survival data with cure fraction that yield valid regression coefficient estimates and inferences were proposed. For a recent review on cure models, see, for example, Amico and Van Keilegom () and Taweab and Ibrahim ().…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, we aim at also expanding the Poly-Weibull model by implementing a version that allows the inclusion of covariates on the ancillary parameters as well as on the location. This effort is also part of a wider plan to bring into survHE more models based on mixtures, e.g., in the form of cure models (Amico and Van Keilegom 2018). This may result in an efficient way of accounting for the underlying complexity of the data generating process, as well as extrapolating the survival curves, potentially including external data.…”
Section: Limitations and Current/future Developments Of Survhementioning
confidence: 99%
“…The cure rate can be treated as a risk score to make treatment decisions in clinical practice, and is a powerful statistic tool for prognostic studies. To identify the existence of a cure subgroup, one common approach is to look at whether there is a long and stable nonzero plateau in the tail of the survival curve 11,12 …”
Section: Introductionmentioning
confidence: 99%